EKSPLORASI PENGALAMAN KARYAWAN MENGENAI BUDAYA KERJA INKLUSIF DI ERA HYBRID WORK PADA PT GMF AEROASIA TBK - Maulana, Indra; Septiyansah, Rizky; Cholis, Akhmad Rokhsan; Muhammad, Riyan; Muttaqijn, Muhammad Imam (Gapenas Publisher, 2024)
This study aims to explore employees' experiences regarding inclusive work culture in the context of hybrid work at PT GMF AeroAsia Tbk. Using a qualitative approach and phenomenological exploration method, data were collected through in-depth interviews, participatory observation, and document analysis. The analysis was conducted using a thematic approach and mapped to Hofstede's cultural dimensions, namely Individualism-Collectivism, Power Distance, and Uncertainty Avoidance. The findings indicate that PT GMF AeroAsia Tbk has implemented various policies to support an inclusive work culture, such as flexible work arrangements and strengthening cross-division communication. However, challenges such as information access gaps, organizational hierarchy, and lack of coordination among employees remain significant obstacles. Hofstede's dimensions helped identify relevant cultural patterns in the implementation of hybrid work, highlighting the importance of team collaboration, reducing power distance, and managing work-related uncertainties. His study offers strategic recommendations, including inclusive leadership training, improved technology accessibility, and the development of hybrid work policies based on inclusivity. Theoretically, this research enriches the literature on inclusive work culture in the hybrid era, while practically providing insights for PT GMF AeroAsia Tbk and other companies facing similar challenges